Impacts of climate change on water provisional services in Tungabhadra basin using InVEST Model. (8th November 2021) - Bejagam, Vijaykumar; Keesara, Venkata Reddy; Sridhar, Venkataramana
Abstract: Water is one of the most important ecosystem services because it is essential for food and energy production. The Tungabhadra basin, located in peninsular India, has a variety of challenges, including inter‐basin water‐sharing issues, low agricultural productivity and value, and rising need for renewable energy production. The Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) water yield model is used to analyze the consequences of climate change on water related services such as water yield and hydropower generation in the densely populated Tungabhadra basin. The impact of climate change on water supply services is studied for the period 1971–2000 as well as the future period 2021–2040. The model is calibrated using streamflow data collected at the Bawapuram gauge station in Telangana and there is a strong correlation between observed and simulated flow. The water yield for the entire basin declined by 33 and 50% under the Representative Concentration Pathways (RCP) 4.5 and 8.5 scenarios, respectively. The RCP 4.5 scenario reduces hydropower production and its Net Present Value (NPV) by 41 to 59%, whereas the RCP 8.5 scenario reduces production and NPV by 56 to 67%. The assessment of ecosystem services at the catchment scale revealed that the basin could be vulnerable to climate change due to a dramatic drop in ecosystem services. The methodology developed in this study can be applied to other river basins where quantifying ecosystem services is critical.